Fiqh-Sufistic: Orthodoxy of Islamic Education in Minangkabau - Satria, Rengga; Rivauzi, Ahmad; ., Nurjanah (KnE Social Sciences, 2024)
The findings of this study reveal that Islamic Education in Minangkabau is heavily influenced by the Islamic Orthodoxy style, which is deeply rooted in classical Arabic texts referred to as the Kitab kuning intellectual tradition. This style of orthodoxy encompasses various fields of knowledge, including theology, jurisprudence (fiqh), and tasawuf (Tarekat Mu’tabarah). The establishment of surau as an Islamic Education Institution in the 18th century AD is historically linked to this style of orthodoxy, which has persisted as the mainstream scientific tradition in madrasas and pesantren in Minangkabau even into the 21st century AD. Notably, through its adherence to Islamic orthodoxy, pesantren education is crucial in fostering religious moderation in Minangkabau. This study employs qualitative methods with historical and phenomenological approaches to analyze the historical documents and phenomena of pesantren in Minangkabau. Data collection techniques include observations, interviews, and documents in the form of manuscripts and archives, while data analysis is carried out through data reduction, presentation, and conclusion. The use of these rigorous and systematic methods ensures the reliability and validity of the findings, which have important implications for the field of Islamic Education in Minangkabau. The subject of this study pertains to Madrasah Tarbiyah Islamiyah Canduang. Keywords: orthodoxy, fiqh-sufistic, Islamic education, Minangkabau